Artificial Intelligence and Moral Progress: A Missing Debate - Tiribelli, Simona (Filosofia Morale/Moral Philosophy, 2024)
This article addresses an underexplored topic in the field of ethics of artificial intelligence (AI), that is, the impact of AI technology on moral progress at the collective level, and shows that such an inquiry is not only ethically relevant but necessary for the design of AI systems able to protect our moral gains and sustain the possibility of further societal moral progress in our contemporary information societies increasingly shaped if not yet governed by AI technology.